2014
DOI: 10.1039/c4cc04183f
|View full text |Cite
|
Sign up to set email alerts
|

Highly cis-selective and lead-free hydrogenation of 2-hexyne by a supported Pd catalyst with an ionic-liquid layer

Abstract: A simple Pd/SiO2 catalyst which was modified with the ionic liquid [BMPL][DCA] gave an excellent yield of 88% towards cis-2-hexene in the stereoselective hydrogenation of 2-hexyne. The catalyst outperforms, even at full conversion, the commonly used lead-poisoned, toxic Lindlar catalyst and supported colloidal-based Pd as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…In many cases such "SCILLs" were found to exhibit substantially enhanced selectivities [1][2][3][4][5][6]. Beneficial effects of the IL layer were demonstrated, for example, for selective hydrogenation using a number of different catalysts, substrates and ILs [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many cases such "SCILLs" were found to exhibit substantially enhanced selectivities [1][2][3][4][5][6]. Beneficial effects of the IL layer were demonstrated, for example, for selective hydrogenation using a number of different catalysts, substrates and ILs [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the use of ionic liquid (IL) thin films as reactivitymodifying coatings has received much attention, both in heterogeneous catalysis [1][2][3][4][5][6] and in electrocatalysis [7][8][9]. The great potential of ILs in such applications arises from their unusual properties, specifically their low volatility, their tunable solvation and miscibility behavior, their high thermal stability and their large electrochemical window [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Thin IL films on high-surface-area solid supports are the key ingredient to highly effective SCILL [52] (Solid Catalyst with Ionic Liquid Layer) and SILP [25,44,49] (Supported Ionic Liquid Phase) catalysis. The groundbreaking discovery in SCILL, for example, was the ability of the IL phase to make the reactive sites of a heterogeneous catalyst more resistant towards poisoning while simultaneously increasing the reactivity and selectivity [52,[58][59][60]. The examples in Figure 1 highlight the fundamental interest in liquid/solid and liquid/gas interfaces and some of the applications mentioned above [11,57,[61][62][63][64][65].…”
Section: Introductionmentioning
confidence: 99%
“…Schwab et al used a supported Pd catalyst with an ionic liquid layer in the stereoselective hydrogenation of 2-hexyne to cis-2-hexene and achieved an outstanding yield of 88%. 30 Babucci et al have reported a class of atomically dispersed supported metal catalysts with performance tuned by ionic liquid coatings, where the coatings controlled the electron density of active metal sites. 40 The inuence of the ionic liquid loading on the activity of the catalyst in the hydrogenation of a-pinene was examined.…”
Section: Resultsmentioning
confidence: 99%
“…Schwab et al reported a highly cisselective and lead-free hydrogenation of 2-hexyne by a supported Pd catalyst with an ionic liquid layer. 30 Hou et al reported on Pd/SiO 2 coated with [DMIM][MeHPO 3 ] for the selective hydrogenation of acetylene. 31 The excellent selectivity of SCILL-based catalysts can be mainly attributed to the lter effect, which regulates the effective concentration of substances at the active sites of catalysts together with the ligand effects of the ionic liquid, which change the electron density distribution of active sites and affect interactions of reactants and intermediates with active metals.…”
Section: Introductionmentioning
confidence: 99%